Pemberantasan Korupsi di Indonesia: Dilema antara Penegakan Hukum dan Kepentingan Politik - H. Siregar, M. Gafur Aditya; M. Sitohang , Agung Perdana; Hayati , Mutiara Azmi; Farisi , Rakhman (Prodi Tata Negara (Siyasah) IAIN Langsa, 2024)
The handling of corruption cases in Indonesia faces various challenges, particularly concerning procedural law and political influence. This study examines how legal processes and political dynamics impact the effectiveness of corruption eradication. The central research question explores the extent to which procedural law regulations and political interventions shape law enforcement outcomes. This study aims to analyze the effects of political interference, law enforcement institutions' independence, and procedural law weaknesses on corruption case handling. This research evaluates relevant legal frameworks and case studies using a qualitative approach that combines normative and empirical legal analysis. The findings reveal that political intervention often undermines law enforcement, while gaps in procedural law create significant obstacles to effective corruption eradication. However, a strong synergy between robust legal policies and genuine political will is essential for enhancing the effectiveness of law enforcement against corruption. The implications of this study underscore the need for legal reforms and institutional safeguards to ensure impartial and effective handling of corruption cases in Indonesia.